solve the following using substitution method.
3x-2y=7
5x-y=3
Answers
Answer:
Solve equation [2] for the variable y
[2] y = -5x + 3
// Plug this in for variable y in equation [1]
[1] 3x - 2•(-5x+3) = 7
[1] 13x = 13
// Solve equation [1] for the variable x
[1] 13x = 13
[1] x = 1
// By now we know this much :
x = 1
y = -5x+3
// Use the x value to solve for y
y = -5(1)+3 = -2
Answer:
System of Linear Equations entered :
[1] 3x - 2y = 7
[2] 5x + y = 3
Graphic Representation of the Equations :
-2y + 3x = 7 y + 5x = 3
Solve by Substitution :
// Solve equation [2] for the variable y
[2] y = -5x + 3
// Plug this in for variable y in equation [1]
[1] 3x - 2•(-5x+3) = 7
[1] 13x = 13
// Solve equation [1] for the variable x
[1] 13x = 13
[1] x = 1
// By now we know this much :
x = 1
y = -5x+3
// Use the x value to solve for y
y = -5(1)+3 = -2
Solution :
{x,y} = {1,-2}